Prolonged Complete Response in a Pediatric Patient With Primary Peripheral T-Cell Lymphoma of the Central Nervous System. (17th November 2015) - Shalabi, Haneen; Angiolillo, Anne; Vezina, Gilbert; Rubenstein, James L.; Pittaluga, Stefania; Raffeld, Mark; Marcus, Leigh
Abstract : We describe a child with a 2-week history of progressive headaches, blurry vision, and intermittent vomiting. Magnetic resonance imaging (MRI) of the brain showed a deep left hemispheric lesion with extension into the corpus callosum. Histology and immunophenotyping of the lesion was consistent with peripheral T-cell lymphoma, not otherwise specified. Chemotherapy was initiated and a complete remission was achieved. This case illustrates that a chemotherapeutic regimen used in adults with central nervous system (CNS) lymphoma can achieve durable remissions in pediatric patients with peripheral T-cell lymphoma, not otherwise specified of the CNS.